“In justice and the public good”: John Laurens and the fight for the Continental Black Battalion - Bettasso, Antoinette Dorothy (Kansas State University, 2021)
In January 1778, John Laurens, an aide-de-camp to General George Washington, sent a letter to his father, Henry Laurens, the then sitting President of the Continental Congress, outlining a plan that had vast society-altering potential had it been carried out. This letter argued that the Continental Army would benefit from enslaved men being allowed to fight in the American Revolution in exchange for their freedom. Laurens, although he was the scion of one of the wealthiest slave-owning families in South Carolina, would seem like an unlikely formulator of such a plan, but this thesis will discuss a series of conditions that allowed for the young officer to conceive of such a plan. These conditions include the complex mix of personal networks, traditional viewpoints and debates, and an education that exposed him to Enlightenment views on slavery. Exploring these conditions yields a far more complicated story than has been told. This thesis will argue that the external factors within John Laurens’ life, influenced by the strong bonds within personal networks, introduced him to ideas not typically found within the Carolina Lowcountry.
Keywords: Revolutionary War; John Laurens; Slavery